2021
DOI: 10.3390/coatings11060648
|View full text |Cite
|
Sign up to set email alerts
|

Affinity between Bitumen and Aggregate in Hot Mix Asphalt by Hyperspectral Imaging and Digital Picture Analysis

Abstract: This study investigated the viability of quantifying the affinity between aggregate and bitumen by means of different imaging techniques. Experiments were arranged in accordance with the rolling-bottle test, as indicated in UNI EN 12697-11, “Test methods for hot bituminous conglomerates—Part 11”. Digital image processing (DIP) techniques have only recently been used for such quantification. The data gathered with a multi-sensor optical platform equipped with VIS–NIR and SWIR spectrometers were compared with DI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…A number of technical observations were made based on the present research, previous trials, and the experiences of other researchers [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ]: Repeatable lighting conditions with uniform lighting and mitigation of shadows are recommended; Careful selection and preparation of the workplace is required to mitigate color contaminated light reflections (e.g., blue color from the sky, other colors from clothes, furniture, etc. ); Precise arrangement of the aggregate particles without visible gaps is highly recommended for reliable classification of the reflective surfaces of asphalt binder; when gaps are present, the background reflects off the asphalt binder, which makes it difficult to distinguish from the binder, regardless of the background color; When artificial lighting is used and color analysis is made, use of lighting with high color reproduction index (CRI) is advised.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A number of technical observations were made based on the present research, previous trials, and the experiences of other researchers [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ]: Repeatable lighting conditions with uniform lighting and mitigation of shadows are recommended; Careful selection and preparation of the workplace is required to mitigate color contaminated light reflections (e.g., blue color from the sky, other colors from clothes, furniture, etc. ); Precise arrangement of the aggregate particles without visible gaps is highly recommended for reliable classification of the reflective surfaces of asphalt binder; when gaps are present, the background reflects off the asphalt binder, which makes it difficult to distinguish from the binder, regardless of the background color; When artificial lighting is used and color analysis is made, use of lighting with high color reproduction index (CRI) is advised.…”
Section: Discussionmentioning
confidence: 96%
“…Based on previous trials and the experiences of other researchers [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ], a methodology for acquiring high-quality photographic data was developed, main principles of which included: Image acquisition under repeatable, controlled, artificial lighting using a ring light; Use of a distinct background color for ease of its removal in post-processing, should it be necessary; Placing the sample aggregates without gaps for mitigating the background reflections; Each sample was photographed once, then it was flipped, and its underside was photographed again to obtain more data per sample; this also would decrease any potential bias of the initial sample arrangement. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be observed that the difference in the coating of the granitic aggregate after 6 h was residual in both tests, while a significant variation was found after 24 h. As mentioned before, the difference in coating percentage after 6 h was only 1%. The uncertainty present in the subjective assessment of this value could be minimized using, for example, a hyperspectral imaging and digital picture analysis, as recently pointed out by Mei et al [30].…”
Section: Aggregate-bitumen Affinity Testmentioning
confidence: 99%
“…Many advanced tests and simulations can be performed to evaluate the quality of the binder-aggregate bonding, such as X-ray photoelectron spectroscopy (XPS) [19,25]; energy dispersive X-ray (EDX) [25]; active adhesion evaluation method (AAEM) [10]; atomic force microscopy (AFM) [26,27]; binder bond strength (BBS) [28]; scanning electron microscopy (SEM) with energy disperse spectroscopy (EDS) [17]; infrared spectroscopy (IR) [13]; optical microscopy (OM) [29], hyperspectral imaging/digital image processing (DIP) [30] and molecular dynamics simulation (MDS) [16,21,24]; in addition to other test methods described by Mehrara et al [2].…”
Section: Introductionmentioning
confidence: 99%